Sustainable Heritage Planning for Urban Mass Tourism and Rural Abandonment: An Integrated Approach to the Safranbolu-Amasra Eco-Cultural Route - Karatas, Emre; Ozkose, Aysun; Heyik, Muhammet Ali (MDPI, 2025)
Urban mass tourism and rural depopulation increasingly threaten heritage sites worldwide, leading to socio-economic and environmental challenges. This study adopts a holistic approach to sustainable tourism planning by examining 84 cultural and natural heritage sites in and around Safranbolu and Amasra, two cities in T & uuml;rkiye that are listed on the UNESCO World Heritage List and the Tentative List. Inspired by historical travelers' itineraries, it proposes an eco-cultural tourism route to create a resilient heritage network. A participatory methodology integrates charettes within Erasmus+ workshops, crowdsourcing, various analysis methods while engaging stakeholders, and AI-powered clustering for route determination. The study follows a four-stage framework: (1) data collection via collaborative GIS, (2) eco-cultural route development, (3) stakeholder participation for inclusivity and viability, and (4) assessments and recommendations. Results highlight the strong potential of heritage assets for sustainable tourism while identifying key conservation risks. Interviews and site analysis underscore critical challenges, including the absence of integrated site management strategies, insufficient capacity-building initiatives, and ineffective participatory mechanisms. Moreover, integrating GIS-based crowdsourcing, machine learning clustering, and multi-criteria decision-making can be an effective planning support system. In conclusion, this study enhances the sustainability of heritage and tourism by strengthening participatory eco-cultural development and mitigating mass tourism and abandonment's negative impacts on the heritage sites.
Keywords: heritage sites; sustainable tourism; eco-cultural rote; multi-criteria evaluation; participatory approach; mass tourism; rural abandonment; Safranbolu; Amasra; CULTURAL-HERITAGE; INDUCED PATHS; CONSERVATION; MANAGEMENT; AREAS; Science & Technology - Other Topics; Environmental Sciences & Ecology